A Psychoanalytic Reflection on Identity, Body and Mask - Conde Alonso, Beatriz (Talía. Revista de estudios teatrales, 2023)
In the psychoanalytic approach the psychological discomfort is tackled from a perspective that does not aim to eliminate the symptom but rather to question it and find out what is involved in its appearance. Even if it may be very annoying, in each person it responds to something particular and in the analysis process it is about -among other things- discovering and gradually dissolving identifications, we could say gradually removing masks, pointing to something else, an own face? Identity as fiction has permeated our Western tradition since its founding, person in ancient greek languaje is prosopon, mask. If human identity is a mask which leaves its impression on the other and hides the true face, what could we expect if the characters do not change? What characters do we have in our culture today? Is there a "true" face? The mask supposes certain freedom since it can be exchanged, can we take it off? It is about addressing these questions through three psychoanalysts and authors: Sigmund Freud, Jaques Lacan and Luce Irigaray. What will be developed briefly are the differences that exist between Freud (1856-1939) and Lacan (1901-1981) and the novelty that Irigaray (1930) proposes to both, all this to think about identity, how much of a face and how much of mask, what do masks mean in the settings and characters that are proposed to us and how the theater echoes this question.